2014
DOI: 10.1021/jf402866q
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glutathione-Enriched Inactive Dry Yeast Preparations on the Stability of Terpenes during Model Wine Aging

Abstract: The impact of the addition of glutathione-enriched Inactive dry yeast preparations (g-IDYs) on the stability of some typical wine terpenes (linalool, α-terpineol, β-citronellol, and nerol) stored under accelerated oxidative conditions was evaluated in model wines. Additionally, the effects of a second type of IDY preparation with a different claim (fermentative nutrient) and the sole addition of commercial glutathione into the model wines were also assessed. Model wines were spiked with the low molecular weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 37 publications
1
43
1
Order By: Relevance
“…Moreover, the levels of nerol were also significantly higher in the GSH 80 wines compared to the control and GSH 5.5 treatments. Other researchers have also found higher levels of certain terpenes in wines exposed to DYP treatments (Andujar-Ortiz et al, 2012;Rodríguez-Bencomo et al, 2014). As the wines in this study were analysed only three months after bottling, the anti-oxidant activities of DYP in preserving certain terpenes, as reported by Rodríguez-Bencomo et al (2014), probably also had such an effect.…”
Section: Controlsupporting
confidence: 58%
“…Moreover, the levels of nerol were also significantly higher in the GSH 80 wines compared to the control and GSH 5.5 treatments. Other researchers have also found higher levels of certain terpenes in wines exposed to DYP treatments (Andujar-Ortiz et al, 2012;Rodríguez-Bencomo et al, 2014). As the wines in this study were analysed only three months after bottling, the anti-oxidant activities of DYP in preserving certain terpenes, as reported by Rodríguez-Bencomo et al (2014), probably also had such an effect.…”
Section: Controlsupporting
confidence: 58%
“…This result indicated that IDY had limited ability to enhance the GSH concentration in kiwi wine, so it could be inferred that the increase of GSH concentration in treated wine was attributed to GSH existed in g‐IDY. This explanation could be supported by Rodríguez‐Bencomo et al who suggested that g‐IDY could indeed release reduced GSH into model wine (Rodríguez‐Bencomo et al, ). Compared with 300 mg/L g‐IDY treated wine, the 20 mg/L GSH treated wine (according to previous experiments in lab, the GSH content in 300 mg g‐IDY was equal to 20 mg GSH) had a significantly lower reduced GSH concentration.…”
Section: Resultsmentioning
confidence: 80%
“…This result is coincident with the GSH concentration reported in present work. Pervious study suggested that there were tripeptides with potential antioxidant properties present in IDY (Rodríguez‐Bencomo et al, ). This might be the reason for improved antioxidant abilities of IDY treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the amount of YD and GSH supplemented in the current experiment and considering that the average content of the latter in inactive dry yeast preparations ranges from a few to ∼12 mg g −1 , it may be hypothesized that the ability of YDs to protect wine color could be not only ascribed to their capacity to release the tripeptide. In opposition, as suggested by other papers, other components of these preparations might be involved with non‐negligible effects.…”
Section: Resultsmentioning
confidence: 84%
“…Inactive dry yeasts (YDs) have been recently included among these complementary tools, probably owing to their similarity to yeast lees. In recent studies, certain of these preparations, whether enriched in glutathione (GSH) or not, demonstrated their protective ability towards aroma compounds in both wine and a model solution . This effect was ascribed to their claimed antioxidant capacity and particularly to their GSH content, and also to the release of selected antioxidant peptides containing methionine, tryptophan and tyrosine …”
Section: Introductionmentioning
confidence: 99%